Ходжа Насреддин: герой чи антигерой, мудрець чи пройдисвіт? - Еврім Олчер Озюнель (Народна творчість та етнографія, 2010)
Some researchers assert that Nasrettin Hodja constitutes a trickster mythology in Turkish culture. There is a tendency among those researchers to simplify Nasrettin Hodja by picturing him as an erotic and a primitive fool. This paper analyzes the Nasrettin Hodja anecdotes in the context of hero/anti-hero discussion, and questions the frame of “trickster” archetype which is generally attributed to the anecdotes. Doing so, it aims at displaying the misunderstanding about the trickster problem and revealing why Hodja cannot be regarded as a trickster archetype or an anti-hero in Turkish culture.